Kejahatan Transnasional Terorganisir di Wilayah Perbatasan: Studi Modus Operandi Penyelundupan Narkotika Riau dan Malaysia - Rendi Prayuda (Department of International Relations, Universitas Andalas, 2020)
The transformation of issues in international politics has led to a shift from traditional security issues (war and military) to non-traditional security issues (human security). One form of non-traditional security threat is the transnational crime activity of narcotics smuggling in Southeast Asia. The Southeast Asian region has an area of around 4.4 million KM2 and is known as the